Panobinostat plus bortezomib and dexamethasone versus placebo plus bortezomib and dexamethasone in patients with relapsed or relapsed and refractory multiple myeloma: a multicentre, randomised, double-blind phase 3 trial - San-Miguel, Jesús F; Hungria, Vânia T M; Yoon, Sung-Soo; Beksac, Meral; Dimopoulos, Meletios Athanasios; Elghandour, Ashraf; Jedrzejczak, Wieslaw Wiktor; Günther, Andreas; Nakorn, Thanyaphong Na; Siritanaratkul, Noppadol; Corradini, Paolo; Chuncharunee, Suporn; et al. (The lancet oncology, 2014)
Panobinostat is a potent oral pan-deacetylase inhibitor that in preclinical studies has synergistic anti-myeloma activity when combined with bortezomib and dexamethasone. We aimed to compare panobinostat, bortezomib, and dexamethasone with placebo, bortezomib, and dexamethasone in patients with relapsed or relapsed and refractory multiple myeloma. PANORAMA1 is a multicentre, randomised, placebo-controlled, double-blind phase 3 trial of patients with relapsed or relapsed and refractory multiple myeloma who have received between one and three previous treatment regimens. Patients were randomly assigned (1:1) via an interactive web-based and voice response system, stratified by number of previous treatment lines and by previous use of bortezomib, to receive 21 day cycles of placebo or panobinostat (20 mg; on days 1, 3, 5, 8, 10, 12, orally), both in combination with bortezomib (1·3 mg/m2 on days 1, 4, 8, 11, intravenously) and dexamethasone (20 mg on days 1, 2, 4, 5, 8, 9, 11, 12, orally). Patients, physicians, and the investigators who did the data analysis were masked to treatment allocation; crossover was not permitted. The primary endpoint was progression-free survival (in accordance with modified European Group for Blood and Marrow Transplantation criteria and based on investigators' assessment) and was analysed by intention to treat. The study is ongoing, but no longer recruiting, and is registered at ClinicalTrials.gov, number NCT01023308. 768 patients were enrolled between Jan 21, 2010, and Feb 29, 2012, with 387 randomly assigned to panobinostat, bortezomib, and dexamethasone and 381 to placebo, bortezomib, and dexamethasone. Median follow-up was 6·47 months (IQR 1·81–13·47) in the panobinostat group and 5·59 months (2·14–11·30) in the placebo group. Median progression-free survival was significantly longer in the panobinostat group than in the placebo group (11·99 months [95% CI 10·33–12·94] vs 8·08 months [7·56–9·23]; hazard ratio [HR] 0·63, 95% CI 0·52–0·76; p<0·0001). Overall survival data are not yet mature, although at the time of this analysis, median overall survival was 33·64 months (95% CI 31·34–not estimable) for the panobinostat group and 30·39 months (26·87–not estimable) for the placebo group (HR 0·87, 95% CI 0·69–1·10; p=0·26). The proportion of patients achieving an overall response did not differ between treatment groups (235 [60·7%, 95% CI 55·7–65·6] for panobinostat vs 208 [54·6%, 49·4–59·7] for placebo; p=0·09); however, the proportion of patients with a complete or near complete response was significantly higher in the panobinostat group than in the placebo group (107 [27·6%, 95% CI 23·2–32·4] vs 60 [15·7%, 12·2–19·8]; p=0·00006). Minimal responses were noted in 23 (6%) patients in the panobinostat group and in 42 (11%) in the placebo group. Median duration of response (partial response or better) was 13·14 months (95% CI 11·76–14·92) in the panobinostat group and 10·87 months (9·23–11·76) in the placebo group, and median time to response (partial response or better) was 1·51 months (1·41–1·64) in the panobinostat group and 2·00 months (1·61–2·79) in the placebo group. Serious adverse events were reported in 228 (60%) of 381 patients in the panobinostat group and 157 (42%) of 377 patients in the placebo group. Common grade 3–4 laboratory abnormalities and adverse events (irrespective of association with study drug) included thrombocytopenia (256 [67%] in the panobinostat group vs 118 [31%] in the placebo group), lymphopenia (202 [53%] vs 150 [40%]), diarrhoea (97 [26%] vs 30 [8%]), asthenia or fatigue (91 [24%] vs 45 [12%]), and peripheral neuropathy (67 [18%] vs 55 [15%]). Our results suggest that panobinostat could be a useful addition to the treatment armamentarium for patients with relapsed or relapsed and refractory multiple myeloma. Longer follow up will be necessary to determine whether there is any effect on overall survival. Novartis Pharmaceuticals.